Effects of commercial microbial inoculants and foliar fertilizers on soybean nodulation and yield in northern Guinea savannah of Nigeria - N’cho, C.; Yusuf, A.A.; Ama-Abina, J.; Jemo, M.; Abaidoo, Robert C.; Savane, I. (2013)
The use of microbial inoculants and less expensive sources of plant nutrients such as foliar fertilizers are ways to practice low-input agriculture, especially in sub-Saharan Africa where smallholder farmers’ soil nutrients are depleted. However, the application of microbial inoculants and foliar fertilizers are influenced by agroecological specific factors. Here we show the effects of microbial inoculants and foliar fertilizers application on soybean, under smallholder farmers’ conditions in northern Guinea savannah. Three microbial inoculants; Bradyrhizobium spp. (RACA 6), arbuscular mycorrhizal fungi (Rhizatech) and Trichoderma harzianum (Eco-T) and two foliar fertilizers; Agroleaf high P and Agrolyser were evaluated. The trial was carried out during 2011 cropping season in randomized complete block design with 12 treatments and 4 replicates. The shoot dry weight was increased separately by the Reference treatment with N, P chemical fertilizers, Rhizatech and RACA 6 + triple superphosphate (TSP) over 21% compared to the control. Significant effect existed among treatments for soybean nodulation and shoot phosphorus concentration. Grain yield was relatively increased by the application of RACA 6 + TSP, RACA 6 + Eco-T + Agrolyser and RACA 6 + Rhizatech + Agrolyser compared to the control. The experiment suggested that soybean co-inoculation with rhizobial and fungal inoculants and application of foliar fertilizers in northern Guinea savannah could lead to improved grain yield.